The Future of Music : Towards a Computational Musical Theory of Everything /: Towards a Computational Musical Theory of Everything. (2020) - Mazzola, Guerino; Noer, Jason; Pang, Yan; Yao, Shuhui; Afrisando, Jay; Rochester, Christopher; Neace, William
No abstract available